A comparative analysis of long-term concrete deformation models of a buttress dam. (15th August 2019) - Ribeiro, Lucas S.; Wilhelm, Volmir E.; Faria, Étore F.; Correa, Jairo M.; dos Santos, Ana Carolina P.
Highlights: A 40-year buttress dam deformation analysis. Data mathematical modeling for dam monitoring. Pattern recognition of seasonal behavior of concrete blocks of buttress dam. This article describes comparison of mathematical modeling of strain meter 40-year data. Abstract: Long-term monitoring is an important topic in assessing the safety and service life of Concrete Dams. Historical data models allow predictions of future behavior of these structures to be made for preventive decision-making. Empirical models use project data to estimate hypothetical behaviors, while numerical models require prior information (actual data) for parameter adjustments. This paper presents a study of four different numerical methods for prediction of concrete deformation using 40-year historical data measured at 5 different strain-meter rosettes of an Itaipu Dam Buttress Block. The results show that ambient temperature-sensitive models as an exogenous variable present a better accuracy (20–50%) in relation to the other two methods, improving the forecasting capability of concrete deformation.